sGC stimulator (BAY 41-8543) combined with PDE9 inhibitor (BAY 73-6691) reduces renal fibrosis in 5/6 nephrectomized rats - Chen, Xin; Delić, Denis; Liu, Yvonne; Cao, Yaochen; Zhang, Zeyu; Wu, Hongwei; Gaballa, Mohamed M. S.; Klein, Thomas; Elitok, Saban; Krämer, Bernhard; Hocher, Berthold (Basic & clinical pharmacology & toxicology, 2025)
Renal fibrosis is closely related to the prognosis of chronic kidney disease (CKD). The increase in cGMP reduces renal fibrosis. Soluble guanylate cyclase (sGC) and phosphodiesterase (PDE) are key enzymes that maintain cGMP levels. BAY 41-8543 (1 mg/kg/day) and/or BAY 73-6691 (1 mg/kg/day) were used to treat 5/6 nephrectomized rats for 13 weeks. 5/6 Nephrectomy caused an increase in cystatin C, proteinuria and glomerulosclerosis and renal interstitial fibrosis. Neither sGC stimulation nor PDE9 inhibition alone improved kidney function and morphology, whereas BAY 41-8543 in combination with BAY 73-6691 attenuated renal interstitial fibrosis. This beneficial effect could not be explained by alterations in blood pressure and the renal immune system. BAY 41-8543 in combination with BAY 73-6691 had no effect on renal macrophage, CD4 + T-cell and CD8 + T-cell in the late-stage of 5/6 nephrectomy. RNA sequencing revealed BAY 41-8543 in combination with BAY 73-6691 down-regulated the expression of fibrosis-related genes such as Collagen Type I Alpha 1, Collagen Type III Alpha 1 Chain and Collagen Type XIV Alpha 1 Chain. sGC stimulator combined with PDE9 inhibitor attenuated renal fibrosis in 5/6 nephrectomized rats by down-regulating fibrosis-related gene expression. This novel approach of using low-dose combination therapies to minimize side effects while maintaining therapeutic efficacy offers a promising strategy for the treatment of CKD.